Chemotherapy-associated Posterior Reversible Encephalopathy Syndrome: A Case Report and Review of the Literature. Issue 6 (November 2016) - How, Joan; Blattner, Margaret; Fowler, Susan; Wang-Gillam, Andrea; Schindler, Suzanne E.
Abstract : Introduction: There are increasing reports of posterior reversible encephalopathy syndrome (PRES) associated with the use of chemotherapeutic agents. Recognition of PRES is crucial given its reversibility with appropriate supportive management. We report a patient presenting with PRES after treatment with Rituximab, Cyclophosphamide, Hydroxydaunorubicin/Adriamycin, Oncovin/Vincristine, Prednisone (R-CHOP) and intrathecal methotrexate. We also perform a systematic review of the literature on chemotherapy-associated PRES. Case Report: A 72-year-old man with recently diagnosed diffuse large B-cell lymphoma became unresponsive 4 days after initiation of R-CHOP and intrathecal methotrexate. Brain magnetic resonance imaging showed interval development of occipital and temporal fluid attenuation inversion recovery hyperintensities consistent with PRES. The patient's blood pressure was aggressively controlled and he received 5 days of high-dose methylprednisone. He subsequently regained consciousness and his mental status gradually improved. Repeat magnetic resonance imaging showed interval resolution of the bilateral fluid attenuation inversion recovery hyperintensities. Review Summary: We performed a systematic review of the literature and included a total of 70 unique cases involving chemotherapy-associated PRES. Platinum-containing drugs, Cyclophosphamide, Hydroxydaunorubicin/Adriamycin, Oncovin/Vincristine, Prednisone/R-CHOP regimens, and gemcitabine were the agents most commonly used in patients who developed suspected chemo-associated PRES. Median onset of symptoms occurred 8 days after chemotherapy. Hypertension was the most commonly reported risk factor associated with the development of chemotherapy-associated PRES. In most cases, PRES improved with supportive management alone within 2 weeks. Conclusions: Chemotherapy-associated PRES is an increasingly encountered syndrome. Both neurologists and non-neurologists should be familiar with the most commonly implicated agents, symptoms, risk factors, and clinical course of chemotherapy-associated PRES, given its favorable prognosis with appropriate management.